Respuesta :
Step-by-step explanation:
Hey, there!!
I hope you mean to subtract (-137) +(-43) from sum of -103 and 27.
First, add -103 + 27
[tex] = - 103 + 27[/tex]
[tex] = - 76[/tex]
{As ( minus + plus )= subtracts with sign which has greator value. }
now,
[tex]( - 137) + ( - 43) = - 180[/tex]
{ minus + minus = add with minus sign}.
Now, subtracting -180 from -76.
=(-76) - (-180 )
Now, multiply the sign (- × -)= +
so, -180 becomes +180
= -76+180
= 104..... is answer.
Hope it helps...
Answer:
104
Step-by-step explanation:
With what you provide, the expression would be:
[tex](-103+27)-(-137+-43)[/tex], which equals to:
[tex](-76)-(-180)= (-76)+(180)=104[/tex]. [negative minus a negative equals positive]
So, the answer would be 104.